Investigating the Performances of Plant-Produced High-Reclaimed Asphalt Pavement Content Warm Mix Asphalts. Issue 28 (December 2018) - Mogawer, Walaa S.; Stuart, Kevin; Austerman, Alexander J.; Soliman, Ahmed A.
Laboratory-based studies have been conducted considering the incorporation of warm mix asphalt (WMA) technologies in paving mixtures both excluding and including reclaimed asphalt pavement (RAP). However, little research has been conducted to date that further advances the knowledge of WMA technologies in combination with high RAP contents beyond experiments using laboratory fabricated mixtures. The objective of this study was to expand on the existing laboratory research by investigating the moisture susceptibility, fatigue cracking and thermal cracking performances of plant-produced mixtures incorporating various WMA technologies and RAP contents. Nine 12.5-mm superpave mixtures were produced in two drum plants using three WMA technologies and three RAP contents. The three WMA technologies used were wax-based SonneWarmix™, chemical-based Evotherm ®, and the Stansteel ACCU-SHEAR™ foaming process. Post production moisture in each mixture was negligible, which means that moisture had no effect on the laboratory mixture performance. The quality of blending analyses showed that the majority of the mixtures had poor blending, which would indicate that there should be performance issues with many of these mixtures. However, the quality of blending had no apparent effect on the laboratory mixture performance. It did not explain any poor performance or any difference in performance. Overall, some WMA with RAP contents up to approximately 50% RAP provided an acceptable laboratory performance. Fatigue cracking was the primary failure mode. Field trials or full-scale pavement accelerated tests with rigorous pavement monitoring are needed to confirm the findings of this study.